Fixed Point Theorems Via Best Approximation - Goyal, A.K. (International Journal of Psychosocial Rehabilitation, 2014)
In this paper, we prove some common fixed point theorems of Gregus type in Banach spaces and give application of our fixed point theorems to best approximation theory. Our work generalizes several earlier results on fixed points in this direction. AMS Subject classification (2000): Primary 54H25, Secondary 47H10